EEG can predict speech intelligibility. (20th March 2019) - Iotzov, Ivan; Parra, Lucas C
Abstract: Objective . Speech signals have a remarkable ability to entrain brain activity to the rapid fluctuations of speech sounds. For instance, one can readily measure a correlation of the sound amplitude with the evoked responses of the electroencephalogram (EEG), and the strength of this correlation is indicative of whether the listener is attending to the speech. In this study we asked whether this stimulus-response correlation is also predictive of speech intelligibility. Approach . We hypothesized that when a listener fails to understand the speech in adverse hearing conditions, attention wanes and stimulus-response correlation also drops. To test this, we measure a listener's ability to detect words in noisy speech while recording their brain activity using EEG. We alter intelligibility without changing the acoustic stimulus by pairing it with congruent and incongruent visual speech. Main results . For almost all subjects we found that an improvement in speech detection coincided with an increase in correlation between the noisy speech and the EEG measured over a period of 30 min. Significance . We conclude that simultaneous recordings of the perceived sound and the corresponding EEG response may be a practical tool to assess speech intelligibility in the context of hearing aids.